Swallows and Amazons [videorecording (DVD)] - Macdonald, Kelly, 1976-; Scott, Andrew, 1976 October 21-; Spall, Rafe, 1983-; Ransome, Arthur, 1884-1967 (Sony Pictures Home Entertainment, 2017)
Four children (the Swallows) on holiday in the Lake District sail on their own to an island and start a war with rival children (the Amazons). In the meantime, a mysterious man on a houseboat accuses them of a crime they did not commit.